HUBUNGAN POLA ASUH TERHADAP KECERDASAN EMOSIONAL ANAK PRA SEKOLAH: LITERATURE REVIEW - Tazkiyatun Nisa Attaufiq Lulu Desara Success; Nabila Khairiyah Putri; Dini Nur Alpiah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Emotional intelligence is an important aspect of a person's life. With emotional intelligence, one is able to manage and understand the feelings of oneself and others. Parenting is an early social interaction for children that is useful for introducing rules, norms and values that apply to society. This study aims to determine the relationship of parenting patterns to the emotional intelligence of pre-school children. Research using the literature review method was carried out using the PICO search in the Google Scholar database. There were 5 journals that met the criteria and showed the results of the relationship between parenting and emotional intelligence of pre-school children.